Community and public health nursing : evidence for practice - Harkness, Gail A., 1939- 4 0 16; DeMarco, Rosanna; 5 (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
We are experiencing extraordinary changes in healthcare in this new century; changes that call upon the most creative, analytical, and innovative skills available. While the world has the resources to reduce health care disparities and eliminate the gaps in health care that exist between various population groups across the globe, accomplishing this is a long term and complicated task. Improvement in the social structure within which people live, and a redistribution of resources so that all people have access to the basic necessities of life, require an unprecedented global consciousness and political commitment--Provided by publisher.
Evidence-Based Practice and Population Health. --;Implementing Nursing Practice in Community Settings. --;Challenges in Community and Public Health Nursing. --;Specialty Practice. The Context of Community and Public Health Nursing. --
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Community health nursing;Public health nursing;Community Health Nursing;Public Health Nursing;Evidence-Based Nursing;Nursing Theory -- United States.;United States.;United States.;United States.;United States.;United States. -- 20; 20; 2